Determinants of work life balance among white collar female in private sector of Bangladesh - Chowdhury, Zerin Momtaz (2019)
Globally booming economy has changed the landscape of workforce in the organizations across the world. Alike Western countries, Asian countries have been observing rapid and significant rise of female in all forms of workforce. Although this empowerment is bringing economic freedom and social identity, several issues confronted by female are weighing down these benefits. One such issue is –work life balance; which depends on the efficient allocation of time and effort between work and other aspects of life. This issue is particularly more crucial to female than male since gracious acceptance of female in work sector merely has lessened their traditional responsibilities towards home and family and their personal life. Again, the perceived notion about work-life balance tends to associate only with married female. Whereas, perennial expectation and workload of organizations have been affecting single and married female’s life with similar intensity in related contexts such as personal and social. Bangladesh, being a developing country, has been observing growth in female workforce in recent years, and work-life balance for female has become a prevalent yet less talked issue there. However, few available literatures recognized this issue but mostly for blue collar female employees. Whereas in reality, white collar working female are also burdened with major challenges to balance their work and life. Therefore, the study was carried out with an aim to investigate the determinants of work life balance among the white collar female employees working in private sector of Bangladesh. The main findings shows personal and family -social life are affected most due to their job and these two determinants can significantly influence overall balance between work and life. Organizational life was found to be overall satisfactory, however changes in few practices can lead to have a better impact on overall work life balance. Based on findings, few recommendations were made to organizations to mitigate problems such as long work hours, insufficient employee benefits, inflexible work arrangements, so that white collar female employees in Bangladesh can maintain better work life balance in. The study highlighted limitations related to online survey and semi-structured interview and scopes for future research activities.